2016
DOI: 10.1007/s00125-016-4107-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single-hormone and dual-hormone artificial pancreas during continuous and interval exercise in adult patients with type 1 diabetes: randomised controlled crossover trial

Abstract: Aims/hypothesis The aim of this study was to assess whether the dual-hormone (insulin and glucagon) artificial pancreas reduces hypoglycaemia compared with the single-hormone (insulin alone) artificial pancreas during two types of exercise. Methods An open-label randomised crossover study comparing both systems in 17 adults with type 1 diabetes (age, 37.2 ± 13.6 years; HbA 1c, 8.0 ± 1.0% [63.9 ± 10.2 mmol/mol]) during two exercise types on an ergocycle and matched for energy expenditure: continuous (60% V : O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 37 publications
0
75
0
3
Order By: Relevance
“…Overall, less hypoglycaemia during daytime hours and exercise was observed with the dual‐hormone artificial pancreas than with a single‐hormone system ; however, results for hypoglycaemia in the overnight period were inconsistent , and the benefits of a dual‐hormone system in reducing mean glucose, for glycaemic control during the prandial period, and for preventing severe hypoglycaemia are unclear.…”
Section: Efficacy and Utility Of Dual‐hormone Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, less hypoglycaemia during daytime hours and exercise was observed with the dual‐hormone artificial pancreas than with a single‐hormone system ; however, results for hypoglycaemia in the overnight period were inconsistent , and the benefits of a dual‐hormone system in reducing mean glucose, for glycaemic control during the prandial period, and for preventing severe hypoglycaemia are unclear.…”
Section: Efficacy and Utility Of Dual‐hormone Systemsmentioning
confidence: 99%
“…An early study of the addition of glucagon to closed‐loop insulin delivery also showed that fewer participants required carbohydrate for treatment of hypoglycaemia in the glucagon group (mean of 1.1 compared with 3.9 treatments per day for dual‐ vs single‐hormone) , and in a three‐way comparison of free‐living adults with Type 1 diabetes performed over 60 h more carbohydrate ingestion for treatment or prevention of hypoglycaemia was observed with both a sensor‐augmented pump (mean of 164 g) and a single‐hormone system (mean of 101 g) than with a dual‐hormone artificial pancreas (mean of 56 g) . Furthermore, in a randomized trial comparing a single‐ and a dual‐hormone system in exercising adults less carbohydrate consumption was observed with the dual‐hormone artificial pancreas . Long‐term studies are needed to evaluate if mini‐boluses of glucagon administered to prevent hypoglycaemia in the dual‐hormone artificial pancreas effectively reduce carbohydrate ingestion and thereby affect body weight.…”
Section: Demonstrated Benefits Of the Dual‐hormone Artificial Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated glucagon delivery combined with exercise announcement has been shown to reduce hypoglycemia. 57 Ideally, a system would be able to automatically detect exercise. Much work has been done to detect exercise through the use of heart rate alone 58,59 or in combination with accelerometry.…”
Section: Future Of Automated Insulin Delivery Systems S-69mentioning
confidence: 99%
“…One option for further improvement might be dual‐hormone artificial pancreas (DHAP) systems which, in addition to insulin, use glucagon to counteract the effect of excessive insulin . The administration of mini‐doses of glucagon in a DHAP system has been shown to be more effective in preventing hypoglycaemia than the suspension of insulin delivery alone, particularly in situations of rapidly decreasing glucose levels, such as late postprandial hypoglycaemia or physical activity . As currently available glucagon formulations show limited stability, daily glucagon renewal is required, making the use of DHAP systems cumbersome .…”
Section: Introductionmentioning
confidence: 99%